Analysing data from patient-reported outcome and quality of life endpoints for cancer clinical trials: a start in setting international standards. Issue 11 (November 2016) - Bottomley, Andrew; Pe, Madeline; Sloan, Jeff; Basch, Ethan; Bonnetain, Franck; Calvert, Melanie; Campbell, Alicyn; Cleeland, Charles; Cocks, Kim; Collette, Laurence; Dueck, Amylou C; Devlin, Nancy; et al.
Summary: Measures of health-related quality of life (HRQOL) and other patient-reported outcomes generate important data in cancer randomised trials to assist in assessing the risks and benefits of cancer therapies and fostering patient-centred cancer care. However, the various ways these measures are analysed and interpreted make it difficult to compare results across trials, and hinders the application of research findings to inform publications, product labelling, clinical guidelines, and health policy. To address these problems, the Setting International Standards in Analyzing Patient-Reported Outcomes and Quality of Life Endpoints Data (SISAQOL) initiative has been established. This consortium, directed by the European Organisation for Research and Treatment of Cancer (EORTC), was convened to provide recommendations on how to standardise the analysis of HRQOL and other patient-reported outcomes data in cancer randomised trials. This Personal View discusses the reasons why this project was initiated, the rationale for the planned work, and the expected benefits to cancer research, patient and provider decision making, care delivery, and policy making.